Relevansi Shiddiq, Amanah, Tabligh, Dan Fathonah Dengan Implementasi Good Corporate Governance Pada Industri Perbankan Syari'ah - Corrina Dian Anita Sari; Hidayatul Farikhah; Mohamad Djasuli (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
This study aims to find out how the Relevance of Shiddiq, Amanah, Tabligh, and Fathonah with the Implementation of Good Corporate Governance in the Sharia Banking Industry. Data collection techniques using document studies, and data analysis using qualitative methods. there are still many challenges that must be faced in implementing the principles of Islamic business ethics in sharia banking so that the synergy of both external and internal stakeholders is needed to overcome these challenges.